Reviews of U.S. Army war crimes trials in Europe, 1945-1948 (National Archives microfilm publications., 1983)
Contains reviews and recommendations pertaining to the 489 war crimes cases tried by U.S. Army courts and commissions between April 1945 and July 1948.